PENGANGKATAN SENTANA RAJEG DALAM PERSPEKTIF HUKUM PERKAWINAN ADAT BALI - Ketut Meta (Jurnal Cakrawala Hukum, 2013)
Adopting sentana rajeg was adopting their own daughter to change the status to be a son. It was because Balipeople followed patrilineal system, in which the descent line was from man line (father) called purusa line.The purpose of adopting sentana rajeg was to continue the next generation, so a family would not mix. So themain purpose was to continue the next generation, especially as the heirs of the person who adopted her.Besides, there was another reason, namely belief of society saying that only a son could deliver the parentsspirits to come into heaven. Sentana rajeg in her marriage, because she had changed the status to be a man, thehusband (the man) should change the status into a woman. In this case, the woman family would proposemarriage to the man family, and later he would be entered to the woman family. Their marriage was callednganyudin marriage, in which the man changed his status to be a woman, and the woman became a man. Thelaw implication from this marriage was the man, since the wedding, did not have a right on inheritance fromhis father, and he would be the heirs from his wifes family. Their marriage was legal if they had done ceremonycalled meperas ceremony, seen by tetua adat and kepala adat, and it had to be announced to all people in thevillage. Along with the legalized sentana rajeg marriage, the husband of sentana rajeg had changed to be thewife and he had entered the environment of sentana rajeg family. As the heirs, he continued to work the landof ayahan desa. Besides, he also had a right to do the duty as sentana rajeg. One of the important things wasto bury the dead body of the parents, including paying the ceremony of dead body burning, and had to keep thehonor of sentana rajeg family.